O duplo grau e os recursos - Magano, Marcelo Camargo (2006)
The present work aims to delimit the essential aspects of double degree of jurisdiction, analyzing it since its creation, in Brazil, up to the current stage of development. Double degree of jurisdiction will be studied in light of constitutional principles. Furthermore, this study will investigate whether or not the possibility of its extinction causes losses to the right of the parties and to the lawsuit. In this context, the advantages and disadvantages of the maintenance of the principle of double degree of jurisdiction are discussed, as well as its relation to the devolutive effect of the appeals. The recognition that it is a constitutional principle does not mean granting an absolute character to it, as the infra-constitutional legislator is responsible for saying how it should effectively act. Ordinary legislators must balance some values (rule of law and procedural effectiveness) when choosing options to inform their legislative activity. From this derives the need to give greater effectiveness to the lawsuit, in opposition to the idea of the lawsuit as a mere technical instrument. Law no. 10352/2001 relatively mitigated the principle of the double degree of jurisdiction, by allowing, in article 515, paragraph 3, of the Code of Civil Procedure, that the court appreciates the grounds of the action, in cases of abatement of action (final judgment), provided that it is a question of law and of fact and there is no need to present evidence in the trial. These changes reveal that jurisdiction must be studied in the perspective of other elements, related to the duration of the lawsuit or by means of mechanisms that guarantee access to justice. Therefore, jurisdiction must be exercised in a more rationalized and effective way for the solution of the legal controversies between the parties. It is considered that timely jurisdiction is more effective than tardy jurisdiction